1997
DOI: 10.1161/01.str.28.9.1739
|View full text |Cite
|
Sign up to set email alerts
|

A Common Polymorphism in the Methylenetetrahydrofolate Reductase Gene, Homocysteine, and Ischemic Cerebrovascular Disease

Abstract: In patients with CVD we confirmed a relationship between the MTHFR genotype and serum homocysteine concentration and an interaction with serum folate concentration. We found no association between CVD and genotype. However, the interaction with serum folate suggests that the genotype could still be a risk factor in populations with a low folic acid intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
3
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(92 citation statements)
references
References 13 publications
2
85
3
2
Order By: Relevance
“…20 In 3 earlier studies, 2 found a significant association between the C677T genotype of MTHFR and cerebral infarction. [5][6][7] If indeed the pathogenic effect of the TT genotype is based only on hyperhomocyst(e)inemia, the MTHFR TT genotype and hyperhomocyst(e)inemia should manifest a more or less similar pattern of association with cerebrovascular disease. In fact, the TT genotype of MTHFR does not always produce hyperhomocyst(e)inemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In 3 earlier studies, 2 found a significant association between the C677T genotype of MTHFR and cerebral infarction. [5][6][7] If indeed the pathogenic effect of the TT genotype is based only on hyperhomocyst(e)inemia, the MTHFR TT genotype and hyperhomocyst(e)inemia should manifest a more or less similar pattern of association with cerebrovascular disease. In fact, the TT genotype of MTHFR does not always produce hyperhomocyst(e)inemia.…”
Section: Discussionmentioning
confidence: 99%
“…2 This might explain the inconsistent results found when the association between the TT mutation of MTHFR and cerebrovascular disease was evaluated. [5][6][7] In severe hyperhomocyst(e)inemia, neurological and vascular manifestations are more pronounced despite less severe hyperhomocyst(e)inemia in patients with severe MTHFR deficiency compared with patients with severe cystathionine ␤-synthase deficiency. 8,9 This suggests that the pathogenic feature of hyperhomocyst(e)inemia with MTHFR deficiency may be different from that of hyperhomocyst(e)inemia alone.…”
mentioning
confidence: 99%
“…Conflicting results regarding candidate gene studies for stroke emphasize the complexity of this multifactorial, complex disorder. Genes encoding for endothelial nitric oxide (eNOS), Apolipoprotein E, as well as candidate genes in the area of homeostasis and thrombosis have been proposed (Carter et al, 1998;Kessler et al, 1997;Markus et al, 1997).…”
Section: Genetic Aspects Of Stroke and Head Traumamentioning
confidence: 99%
“…14,15 The findings from the small number of prospective studies that have addressed associations between tHcy concentrations and incident coronary heart diseases (CHD) or stroke are inconsistent [16][17][18][19][20][21][22] Homozygosity for a defective thermolabile variant of MTHFR, a common genetic polymorphism which results in hyperhomocysteinemia, has not been consistently linked with cardiovascular disease endpoints. 23,24 Although the importance of gene markers will vary depending on relevant environmental exposures, diet in this instance, the findings from gene association studies conducted to-date are distinctly unimpressive. The biological plausibility of the tHcy-vascular disease hypothesis rests partially on studies that have used unphysiologically high doses of homocysteine.…”
Section: Thcy and Cardiovascular Diseasementioning
confidence: 99%